PENGARUH DAYADUKUNG LAHAN DAN FAKTOR SOSIAL EKONOMI TERHADAP PERILAKU PETANI DALAM KONSERVASI LAHAN SAWAH DI KABUPATEN KULON PROGO - Dian Kurniasih; Roso Witjaksono; Jamhari Jamhari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2007)
The research aimed to determine: (1)farmer s behavior on wet land conservations in Kulon Progo Regency (2) Tht:impact of land carrying capacity and socio economicfactors tofarmer s behavior on wet land conservations, and (3) The impact offarmer s behavior on wet land conservations to their agribusiness income.The method used in this study was descriptive analysis. The research was done in Kulon Progo Regency, especially in Nanggulan and Kokap Sub District. The locations chose bypurposive sampling method to represent area that have high level of land carrying capacity and low level of land carrying capacity. The respondents chose by multistage random sampling method. Farmers behavior on wet land conservations measured with Proportion Test by Dajan. Therefore, the impact of land carrying capacity and socio economicfactors to farmer s behavior on wet land conservations, and the impact of farmer s behavior on wet land conservations to the farmer s agribusiness income measured with multiple linear regression analysis.The results indicated that more than 50%farmers in Kulon Progo regency have a high level of conservations behavior, especially in vegetative methods. Mechanics methods were in middle level. The level of land carrying capacity did not influence farmer's behavior on wet land conservations. Farmers in both area have a high level behavior on wet land conservations. Thesocio economicfactors influenced thefarmer s behavior on wet land conservations significantly were age, conservation knowledge, motivation, activity in group, non agribusiness income, availability of organics input and leadership. The high level of farmer s behavior on wet land conservations did not influence their agribusiness income. But the relationship was positive, the more increase offarmer s behavioronwetland conservations, themore farmer s agribusiness income.Key words: Land Carrying Capacity, Socio Economic Factors, WetLand Conservations, Agribusiness Income